Kemampuan Pemecahan Masalah Matematis Siswa dalam Menyelesaikan Soal PISA pada Topik Geometri - Anas Ma'ruf Annizar; Mohammad Archi Maulyda; Gusti Firda Khairunnisa; Lailin Hijriani (Universitas Hamzanwadi, 2020)
This study aims to describe the mathematical problem-solving ability of students in solving geometry problem of Programme for International Student Assessment (PISA). Subjects were selected by considering the result of the mathematics ability of 53 students in grade X through a preliminary problem. Then, the students was grouped into 3 categories: high-skilled subject, medium-skilled subject, and low-skilled subject. From each categories, the researchers picked one student as a research subject considering their communication skills to make researcher easy to describe the subects’ process in solving the problem. The research was held by give each subject a geometry problem that is adapted from PISA problem, and then the researchers provide an interview for each subject. The results of this study analyzed by a descriptive qualitative method. The results showed that the high-skilled subject abled in understanding the problem, planning, and implementing strategy properly, as well as looking back in the calculation section. For the medium-skilled subject already made mistakes in understanding and planning the problem, so that the subject implemented the wrong strategy, besides the subject corrected to the concept only. The low-skilled subject made mistakes in understanding and planing the problem so that the subject implemented the wrong strategy. In addition, the low-skilled subject did not look back at his work.